O memorial do colégio Manoel Ribas: um diagnóstico para o planejamento museológico - Romero, Maria Helena Nascimento (2017)
The present study aims to point out guidelines for the elaboration of a plan of the Memorial Museum of the College Manoel Ribas to consolidate it as a space for research, production of knowledge and education. Justified the choice of this theme, first, by the fact that the College is one of the few institutions of basic education that has a museum. On the other hand, the existence of 11,904/2009 Law, which established the Brazilian Museums Statute (Articles 44, 45, 46 and 47), makes it compulsory to elaboration and implementation of the Museological Planning. Thus, it is necessary the construction of a specific study that points to the guidelines for the preparation of a Museological Planning with a view to promoting actions of preservation, conservation and dissemination of the College's Memorial Manoel Ribas, as well as analyze your inclusion in the educational context Santamariense, highlighting it as cultural heritage and space of memory formation and regional identity. To this end, we used a qualitative approach from a case study on the Memorial. The bibliographic and documentary research, seeking to demonstrate the importance of the collection of the Memorial as the heritage school. The research was done thorough readings in scientific articles, newspaper reports and other academic papers. This proposal of the construction of the Museological Planning for the institution, considers mainly the possibility and feasibility of your effective application, being also the planning presented as a product of this dissertation for the Postgraduate Program on Cultural Heritage of the Federal University of Santa Maria (PPGPPC/UFSM).